Timing of active left ventricular unloading in patients with cardiogenic shock on veno-arterial extracorporeal membrane oxygenation therapy. (3rd October 2022) - Schrage, B; Sundermeyer, J; Blankenberg, S; Eitel, I; Kirchhof, P; Mangner, N; Moebius-Winkler, S; Orban, M; Thiele, H; Morrow, D A; Schulze, P C; Westermann, D
Abstract: Aim: To evaluate the impact of timing of active left ventricular (LV) unloading in relation to veno-arterial extracorporeal membrane oxygenation (VA-ECMO) implantation on outcomes of patients with cardiogenic shock (CS). Methods and results: Data from 421 patients with CS treated with active LV unloading on top of VA-ECMO at 18 tertiary-care centers in 4 countries were collected. Only patients in whom both devices were implanted within 24 hours of each other were considered and patients were stratified by timing of device implantation in early vs. delayed active LV unloading (e.g. active LV unloading before vs. after VA-ECMO). Cox and logistic regression models (adjusted for age, sex, lactate, cardiopulmonary resuscitation (CPR), VA-ECMO assisted CPR and enrollment center) were fitted to evaluate the association between early active LV unloading and 30-day mortality as well as several safety outcomes. Overall, 310 (73.6%) patients were treated with early active LV unloading. Early active LV unloading was associated with a lower 30-day mortality risk (hazard ratio 0.63, 95% confidence interval 0.46–0.87) and a higher likelihood of weaning from mechanical ventilation (odds ratio 1.25, 95% confidence interval 1.03–1.52), but not with more complications. Importantly, postponing active LV unloading in these patients was associated with higher mortality risk (Figure 1), and lower likelihood of successful weaning from mechanical ventilation. Conclusion: This exploratory study lends support to the use of early active LV unloading in CS patients on VA-ECMO as a primary treatment strategy, as opposed to a bail-out approach. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Unrestricted research grant from Abiomed